Avicenna questions of geometric optics (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The article briefly reveals some of the views of the famous medieval scientistencyclopedist Abu Ali ibn Sina (Avicenna, 980-1037) about acoustics in Physics. Based on the study of natural sciences from the physical part of the treatise "Sawdust of Nature" ("Kurozai Tabiyet"), specially dedicated to acoustics.It is characteristic that it is in this treatise that Avicenna treats some problems of acoustics from the point of view of the "science of nature" Physics" of that tim. In the medieval East, many prominent scientists addressed the problems of acoustics: such as Abu Nasr al-Farabi, Abu Ali ibn al-Haysam and Avicenna himself. It received a special development in the Middle Ages in connection with the development of music theory issues. It was also considered in a philosophical aspect. The article has an interdisciplinary character, written at the junction of the subject of physics and history, taking into account historical and scientific analysis